Reactions to ethical dilemmas: A study pertaining to certified public accountants - Claypool, G. A. (Journal of business ethics, 1990)
This study discusses how perceptions of ethics are formed by certified public accountants (CPAs). Theologians are used as a point of comparison. When considering CPA ethical dilemmas, both subject groups in this research project viewed ‘confidentiality’ and ‘independence’ as more important than ‘recipient of responsibility’ and ‘seriousness of breach’. Neither group, however, was insensitive to any of the factors presented for its consideration. CPA reactions to ethical dilemmas were governed primarily by provisions of the CPA ethics code; conformity to that code may well be evidence of higher stage moral reasoning.